Peran Bagian Organisasi Terhadap Peningkatan Budaya Kerja Di Lingkungan Sekretariat Daerah Pemerintah Kabupaten Ciamis - Rafyanzha Satria Wicaksana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The background of this research is the not yet optimal work culture in the Ciamis Regional Secretariat and how the role of the Regional Secretariat Organizational Section has in improving work culture in the Government environment. The purposes of this research are: 1) To find out and analyze the role of the Organizational Section of the Regional Secretariat of the Ciamis Regency Government 2) To find out and analyze the work culture at the Regional Secretariat of Ciamis Regency, 2) To find out the role of the Organizational Section in improving work culture within the Regional Secretariat Ciamis Regency Government. The research method used is descriptive method with a qualitative approach. This study attempts to describe the role of the Regional Secretariat Organizational Section in improving work culture within the Ciamis District Government Regional Secretariat. The approach that researchers use is a qualitative naturalistic approach. In this approach will be more concerned with the process than the results. Data collection techniques in this study through observation, interviews, and documentation. The informants in this study were the Head of the Organizational Section, the head of the work team 1, the head of the work team 2, the executor 1, the executor 2, and the implementer 3 of the Organizational Section of the Regional Secretariat of Ciamis Regency. bResults of the study show that 1) The role of the Organizational Section at the Regional Secretariat of Ciamis Regency is to always develop various techniques to open opportunities for success in achieving work program objectives as well as agency plans and targets, one of which is to optimize coordination with the OPD within the Ciamis Regency Government to always coordinate and carry out consultation with the Provincial Government of West Java and the Central Government, 2) The work culture in the Regional Secretariat of Ciamis is ACTIVITY. In terms of attitude, there are still skills and attitudes that are lacking from some employees, it is already seen that they have enthusiasm, work hard, are honest and are not lazy. In the behavior of employees who have shown a serious attitude at work, but there are also some employees who are not innovative and work discipline is good, it can be seen from the employees who are never late and comply with the rules that apply in the agency. But the collaboration has not been maximized between cooperation with other OPDs in making SOPs. 3) The Role of the Organizational Section for Improving Work Culture in the Regional Secretariat of the Ciamis Regency Government is that every year it has a monitoring and evaluation team for the continuity of work cultural values that exist in each regional apparatus organization (OPD) and every year there is always a process socialization and internalization from the Organizational Section to each Regional Apparatus Organization (OPD). The form of efforts made to overcome these problems is by involving employees in formal education and training, providing direction or coaching to each personal according to their respective duties, involving employees in technical training, providing direction and coaching to employees who do not understand organizational goals in stages and stages, increasing employee competence and improving internal control comprehensively.